Potential of chopped heath biomass and spent growth media to replace wood chips as bulking agent for composting high N-containing residues. (15th July 2017) - Viaene, J.; Reubens, B.; Willekens, K.; Van Waes, C.; De Neve, S.; Vandecasteele, B.
Abstract: We investigated the potential of C-rich byproducts to replace wood chips as bulking agent (BA) during composting. The impact of these alternatives on the composting process and on compost stability and characteristics was assessed. Three BA (chopped heath biomass and spent growth media used in strawberry and tomato cultivation) were used for processing leek residues in windrow composting. All BA resulted in stable composts with an organic matter (OM) content suitable for use as soil amendment. Using chopped heath biomass led to high pile temperatures and OM degradation and a nutrient-poor compost with high C/P ratio appropriate for increasing soil organic carbon content in P-rich soils. Spent substrates can replace wood chips, however, due to their dense structure and lower biodegradation potential, adding a more coarse BA is required. Generally, the nutrient content of the composts with growth media was higher than the composts with wood chips and chopped heath biomass. Graphical abstract: Highlights: Chopped heath and spent growth media can be used as bulking agents. Chopped heath compost has a high OM content and C/P ratio. Clear differences in N immobilization between bulking agents were observed. NIRS can monitor quickly the chemical properties and stability during composting.